Advantages of FBPA PET in evaluating early response of anti-PD-1 immunotherapy in B16F10 melanoma-bearing mice: Comparison to FDG PET - Tatsumi, Mitsuaki; Soeda, Fumihiko; Naka, Sadahiro; Kurimoto, Kenta; Ooe, Kazuhiro; Fukui, Hideyuki; Katayama, Daisuke; Watabe, Tadashi; Kato, Hiroki; Tomiyama, Noriyuki (Frontiers in Oncology, 2022)
Purpose: PET with L-4-borono-2-[18F]fluoro-phenylalanine (FBPA) was reported to be useful to differentiate malignant tumors and inflammation. Although immunotherapy with immune checkpoint inhibitors (ICIs) has been applied to cancer treatment recently, FDG PET may not be suitable to determine the effect of ICIs because of false-positive findings caused by treatment-related inflammation. In this study, we aimed to demonstrate that FBPA PET allowed detection of the early response of anti-PD-1 immunotherapy in tumor-bearing mice, comparing the results with those of FDG PET. Methods: Mice with B16F10 melanoma xenografts were prepared. Anti-mouse PD-1 antibody or PBS was administered twice intraperitoneally to the tumor-bearing mice on Day 0 (3 days after inoculation) and Day 5 (treatment or control group ). PET/CT imaging was performed twice for each mouse on Day 0 before the anti-PD-1 antibody/PBS administration and on Day 7 using a micro-PET/CT scanner. FBPA and FDG PET/CT studies were conducted separately. SUVmax and the tumor to liver ratio (T/L ratio) were used as parameters exhibiting tumor activity. Tumor uptake volume (TUV) and metabolic tumor volume (MTV) were also calculated for FBPA and FDG, respectively. Changes between pre- and posttreatment SUVmax or T/L ratio were observed using the formula as follows: [(posttreatment parameter values/pretreatment values - 1) × 100] (%). Results: Tumors in TrG were smaller than those in CoG on Day 7. SUVmax and T/L ratio represented no differences between TrG and CoG in FBPA and FDG PET before treatment. FBPA PET on Day 7 demonstrated that SUVmax, T/L ratio, and TUV in TrG were statistically smaller than those in CoG. %T/L ratio and %SUVmax exhibited the same trend in FBPA PET. However, FDG PET on Day 7 revealed no differences in all parameters between TrG and CoG. T/L ratio and %SUVmax in TrG represented larger values than those in CoG without statistical significances. Conclusion: This study demonstrated that FBPA PET allowed detection of the early response of anti-PD-1 immunotherapy in B16F10 melanoma-bearing mice. FDG PET did not detect the response. Further studies are required to determine whether FBPA PET is useful in evaluating the treatment effect of ICIs in humans.